Andromeda XXI – a dwarf galaxy in a low-density dark matter halo. Issue 4 (7th June 2021) - Collins, Michelle L M; Read, Justin I; Ibata, Rodrigo A; Rich, R Michael; Martin, Nicolas F; Peñarrubia, Jorge; Chapman, Scott C; Tollerud, Erik J; Weisz, Daniel R
ABSTRACT: Andromeda XXI (And XXI) has been proposed as a dwarf spheroidal galaxy with a central dark matter density that is lower than expected in the standard Λ cold dark matter (Λ CDM) cosmology. In this work, we present dynamical observations for 77 member stars in this system, more than doubling previous studies to determine whether this galaxy is truly a low-density outlier. We measure a systemic velocity of v_r=-363.4± 1.0 km s^-1 and a velocity dispersion of σ _v=6.1^+1.0_-0.9 km s^-1, consistent with previous work and within 1σ of predictions made using the modified Newtonian dynamics framework. We also measure the metallicity of our member stars from their spectra, finding a mean value of [Fe/H]=-1.7± 0.1 dex. We model the dark matter density profile of And XXI using an improved version of gravsphere, finding a central density of ρ _DM(150 pc)=2.6_-1.5^+2.4 × 10^7 M_ kpc^-3 at 68 per cent confidence, and a density at two half-light radii of ρ _DM(1.75 kpc)=0.9_-0.2^+0.3 × 10^6 M_ kpc^-3 at 68 per cent confidence. These are both a factor of3\!-\!5 lower than the densities expected from abundance matching in Λ CDM. We show that this cannot be explained by 'dark matter heating' since And XXI had too little star formation to significantly lower its inner dark matter density, while dark matter heating only acts on the profile inside the half-light radius. However, And XXI's low density can be accommodated within Λ CDM if it experienced extreme tidal stripping (losing 95 per cent of its mass), or if it inhabits a low-concentration halo on a plunging orbit that experienced repeated tidal shocks.